PEMENUHAN HAK PEKERJA TETAP PT. PROPERTRUST INDONESIA - Nexie Nurafifah; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The employment relationship between workers and employers is based on a work agreement, for a work agreement to be realized properly, the rights andobligations that have been agreed upon must be fulfilled by the parties to theagreement. In PT Propertrust Indonesia, which is a company engaged in theproperty sector, which has five permanent workers, but none of the five permanentworkers have fulfilled their rights in accordance with the company's workagreement that has been determined. The formulation of the problem in this thesisis how to analyze the implementation of the fulfillment of the rights of permanentworkers based on the employment agreement of PT. Propertrust Indonesia andwhat are the factors inhibiting permanent workers of PT. Propertrust Indonesiain obtaining their rights.This type of research is a sociological research because with this researchthe author directly conducts research on the location or place under study in orderto provide a complete and clear picture, while the population and sample areHuman Resources Development (HRD) PT. Propertrust Indonesia and permanentemployees of PT. Indonesian property trusts. The purpose of this study was todetermine the implementation of the fulfillment of rights based on the workagreement of PT. Propertrust Indonesia and the barriers to permanent workers ofPT. Propertrust Indonesia in obtaining its rights.The result of this research is the implementation of the fulfillment of therights of permanent workers based on the work agreement of PT. PropertrustIndonesia has not been fulfilled, as evidenced by the absence of a single permanentemployee of PT. Propertust Indonesia whose rights are fulfilled in the form of fees.This is not in line with the work agreement of PT. Propertrust Indonesia which hasbeen agreed by the company with permanent workers with the number:001/PT/PKWTT/V/2019, as well as the inhibiting factors for permanent workersin obtaining their rights from companies and permanent workers. Suggestion fromthe author for the parties involved in labor relations must understand and carryout their rights and obligations correctly to create a fair working relationship forthe parties, and it is hoped that those in the company who have the highestauthority can lead companies with good managerial skills, employers or thegovernment must provide job training and guarantees for the continuity ofpermanent workers and if problems arise in labor relations, they must be resolvedfairly